B cell TLR1/2, TLR4, TLR7 and TLR9 interact in induction of class switch DNA recombination: Modulation by BCR and CD40, and relevance to T-independent antibody responses. (February 2015) - Pone, Egest J.; Lou, Zheng; Lam, Tonika; Greenberg, Milton L.; Wang, Rui; Xu, Zhenming; Casali, Paolo
Abstract Ig class switch DNA recombination (CSR) in B cells is crucial to the maturation of antibody responses. It requires IgH germline IH-CH transcription and expression of AID, both of which are induced by engagement of CD40 or dual engagement of a Toll-like receptor (TLR) and B cell receptor (BCR). Here, we have addressed cross-regulation between two different TLRs or between a TLR and CD40 in CSR induction by using a B cell stimulation system involving lipopolysaccharides (LPS). LPS-mediated long-term primary class-switched antibody responses and memory-like antibody responses in vivo and induced generation of class-switched B cells and plasma cells in vitro. Consistent with the requirement for dual TLR and BCR engagement in CSR induction, LPS, which engages TLR4 through its lipid A moiety, triggered cytosolic Ca2+ flux in B cells through its BCR-engaging polysaccharidic moiety. In the presence of BCR crosslinking, LPS synergized with a TLR1/2 ligand (Pam3CSK4) in CSR induction, but much less efficiently with a TLR7 (R-848) or TLR9 (CpG) ligand. In the absence of BCR crosslinking, R-848 and CpG, which per se induced marginal CSR, virtually abrogated CSR to IgG1, IgG2a, IgG2b, IgG3 and/or IgA, as induced by LPS or CD154 (CD40 ligand) plus IL-4, IFN-γ or TGF-β, and reduced secretion of class-switched Igs, without affecting B cell proliferation or IgM expression. The CSR inhibition by TLR9 was associated with the reduction in AID expression and/or IgH germline IH-S-CH transcription, and required co-stimulation of B cells by CpG with LPS or CD154. Unexpectedly, B cells also failed to undergo CSR or plasma cell differentiation when co-stimulated by LPS and CD154. Overall, by addressing the interaction of TLR1/2, TLR4, TLR7 and TLR9 in the induction of CSR and modulation of TLR-dependent CSR by BCR and CD40, our study suggests the complexity of how different stimuli cross-regulate an important B cell differentiation process and an important role of TLRs in inducing effective T-independent antibody responses to microbial pathogens, allergens and vaccines.